The life after marriage: Hmong young women, agriculture and technology in Vietnam - Kawarazuka, Nozomi (International Potato Center, 2018)
Presented by Nozomi Kawarazuka (CIP), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.